(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aims to analyze the impact of audit committees in banks on reducing the risk of non-compliance with laws, instructions, and regulations, and the impact this relationship has on the bank’s reputation and financial transactions. A questionnaire consisting of 35 forms was distributed to a group of external and internal auditors in a number of private Iraqi banks .A descriptive and inferential methodology was used to describe and test relationships and hypotheses. The study reached a set of conclusions, the most important of which are: The role of audit committees is to confirm the accuracy of the accounting data and information contained in financial reports, and that audit committees play a positive role in assessing the level of regulatory compliance.